Frontiers of Economic Policy Communications - Stankova, Olga Ilinichna (Departmental Papers; Departmental Paper ;, 2019)
The paper provides an overall view of communications across various areas of economic policy, aiming to help country authorities as they increasingly use communications as a policy tool in its own right. The paper identifies frontier communications challenges, drawing on a large body of research on the salient issues. Although communications can never be a substitute for good policies, economic reforms are more likely to fail or even be reversed if they are not understood or accepted by those whom they affect.